The Role of Brucella abortus I-206 Thermoextracts in L- and S-form in Shaping the Immune Response in White Mice - V. I. Dubrovina; T. P. Starovoitova; S. A. Vityazeva; N. L. Barannikova; T. A. Ivanova; G. B. Mukhturgin; A. V. Gromova; G. Yu. Sorkina; S. V. Balakhonov (Эпидемиология и вакцинопрофилактика, 2019)
Background. Brucellosis is an acute infectious-allergic zoonotic disease in which sick farm animals are the main source of infection for humans. Immunization of animals and people on the territory of Russia is carried out by live vaccines, which, having a high immunogenicity, can cause clinical, hematological and immune changes. Therefore, the work on the design of new vaccines that provide high protection and do not possess reactogenicity, agglutinogenic and sensitizing activity is the current direction of the study. Methodology. The study was performed on 72 outbred white mice immunized with inactivated B. abortus 19 ВA vaccine and thermal extracts (TE) of B. abortus I-206 in L- and S-form. Morphofunctional changes in the regional lymph node, spleen, and thymus of experimental animals were examined on days 3, 7, 14, and 21 of the time of immunization. Results.The influence of single introductions thermoextracts B. abortus I-206 in L-and S-form in comparison with inactivated vaccine B. abortus 19 ВА. the removal or the morphohistologic indices of immune organs of experimental animals. Found that thermoextracts have the ability to activate immune adjustment within the structures of the spleen and lymph nodes, without causing side effects, including allergic reactions. Conclusions. Preparations obtained from B. abortus in the L- and S-forms have the ability to activate immunological rearrangement in immunocompetent organs without causing any side effects. The results indicate the promise of further research in this direction.